Inexpensive protein overexpression driven by the NarL transcription activator protein. Issue 6 (6th March 2022) - Hothersall, Joanne; Lai, Sandie; Zhang, Nan; Godfrey, Rita E.; Ruanto, Patcharawarin; Bischoff, Sarah; Robinson, Colin; Overton, Tim W.; Busby, Stephen J. W.; Browning, Douglas F.
Abstract: Most Escherichia coli overexpression vectors used for recombinant protein production (RPP) depend on organic inducers, for example, sugars or simple conjugates. However, these can be expensive and, sometimes, chemically unstable. To simplify this and to cut the cost of RPP, we have developed vectors controlled by the Escherichia coli nitrate‐responsive NarL transcription activator protein, which use nitrate, a cheap, stable, and abundant inorganic ion, to induce high‐level controlled RPP. We show that target proteins, such as green fluorescent protein, human growth hormone, and single‐chain variable region antibody fragments can be expressed to high levels using our promoter systems. As nitrate levels are high in many commercial fertilizers, we demonstrate that controlled RPP can be achieved using readily available and inexpensive garden products. Abstract : Most Escherichia coli overexpression vectors used for recombinant protein production (RPP) depend on organic inducers, such as IPTG, which can be expensive and chemically unstable. To cut the cost of RPP, Hothersall and co‐workers have developed new expression systems, which use nitrate, a cheap, stable and abundant inorganic ion, to induce high‐level RPP. As nitrate levels are high in many commercial fertilizers, they demonstrate that controlled RPP can even be achieved using inexpensive garden products purchased from any local store.